The participation of the popular sectors in the revolutionary war and its link with politics; Tucumán in 1815 - Lupiañez, Gabriela Paula (2021)
The objective of this article is to make visible the militarized popular sectors in the political arena of the city of Tucumán, in the Provincias Unidas del Río de la Plata, Argentina. It focuses on the popular mobilization produced in 1815 that confronted two political groups. From the analysis of this case, it can be said that the political participation of popular sectors in political contests was earlier than the one reported in the local historiography, besides previous experiences of militarization in Tucuman are collected. The appeal to the rural popular sectors with the principle of popular sovereignty allowed the group led by the “revolutionary governor” to legitimize its position with respect to the “traditional” representation of the cabildo.